2008
DOI: 10.1653/0015-4040(2008)91[446:psacoc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Population Survey and Control of Chironomidae (diptera) in Wetlands in Northeast Florida, USA

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
5
1
1
Order By: Relevance
“…Adult emergence has been considered only in some studies on the effects of Bti on chironomids (Liber et al, 1998, Craggs et al, 2005, Ali et al, 2008. Our results showed that Bti had no significant effect on the emergence of both P. nubifer and T. curticornis.…”
Section: Discussioncontrasting
confidence: 47%
“…Adult emergence has been considered only in some studies on the effects of Bti on chironomids (Liber et al, 1998, Craggs et al, 2005, Ali et al, 2008. Our results showed that Bti had no significant effect on the emergence of both P. nubifer and T. curticornis.…”
Section: Discussioncontrasting
confidence: 47%
“…Since Bti was initially described and applied to control mosquito larvae (Goldberg and Margalit 1977), Bti-based products have been used to control many mosquito (Goldberg and Margalit 1977; Margalit and Dean 1985; Amalraj et al 2000; Fillinger et al 2003) and chironomid species (Lei et al 2004, 2005; Ali et al 2008) worldwide. To date, some effective commercial Bti products have been registered for dipteran insect control (Russell and Kay 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Adult emergence of chironomid midges can occur at nuisance levels in areas surrounding urban and suburban aquatic habitats (Ali 1996). At a shallow wetland in northeast Florida, USA, chironomid populations have existed for several months each year at nuisance levels that interfere with human activities, necessitating control measures (Ali et al 2008). Chironomus kiiensis Tokunaga has been reported to be the most prevalent chironomid species in Korea out of about 50 species recorded to date (Ree 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, existen datos contrastantes en los que en cultivos artificiales y lagunas naturales se pueden encontrar abundancias de Clunio de hasta el 76 y 95%, respectivamente, en relación con el total de invertebrados recolectados (Navarrete et al, 2004;Espinoza y Morales, 2008); mientras que en nuestro estudio, Clunio representó menos del 1%. La presencia de este género en los ecosistemas es de gran relevancia por su papel como reciclador de nutrientes y fuente de alimento para especies carnívoras, siendo un factor determinante en la productividad de los ecosistemas (Cranston, 1995;Brodin y Andersson, 2009); sin embargo, es importante que las condiciones ambientales mantengan en control su densidad, ya que los casos en que su presencia es de tipo invasora o hay un aumento desmedido de la población son potencialmente perjudiciales, pudiendo desplazar a especies locales, provocar pérdidas económicas por daños estructurales a infraestructura costera y generar eventos reproductivos nocivos para el hombre, convirtiéndose en un problema de salud pública y ambiental (Alí et al, 2008). De aquí que el conocimiento de su dinámica poblacional sea tan importante, llegando incluso a utilizarse como indicadores del estado de salud de los ecosistemas (Lobinske y Alí, 2006;Alí et al, 2008).…”
Section: Bimestresunclassified